تحريف تطبيق الوصايا العشر لليهودية - Muhammad Hudaya; Novi Hidayat (Universitas Darussalam Gontor, 2019)
Among the sharia in Judaism is the ten commandments of God. Where the commandment has a high place in the Jewish religion. The Commandement is a life guideline in socializing with the community, whether in religious or social affairs. But Jews were not practicing the commandments. They believed more of the teachings brought by the Rabbis (Jewish ministers) compared to the ones listed in the Torah and the commandments. Consequently, many misappropriation, violence, and murder are caused by it. Based on this fact researchers want to further examine what the actual meaning of the commandment is and how does the distortion occur in it? The result of this research is 10 commandments that contain a very meaningful value. The deviation originated from the rewriting of the Torah after the death of the Prophet Moses. Besides, there is a reinterpretation of the Torah. The interpretation is the result of the thought of the Jewish priests who merely appetites to lust.